New Dualities of Supersymmetric Gauge Theories - Teschner, J. (Mathematical Physics Studies, 2016)
Exact results on N = 2 supersymmetric gauge theories -- Families of N = 2 field theories -- Hitchin systems in N = 2 field theory -- A review on instanton counting and W-algebras -- b-deformed Matrix Models and 2d/4d correspondence -- Localization For N = 2 Supersymmetric GaugeTheories in Four Dimensions -- Line operators in supersymmetric gauge theories and the 2d-4d relation -- Surface Operators -- A review on SUSY gauge theories on S3 -- 3d Superconformal Theories from Three-Manifolds -- Supersymmetric gauge theories, quantization of Mflat, and conformal field theory -- Gauge/Vortex Duality and AGT -- B-Model Approach to Instanton Counting.